2018
DOI: 10.1159/000491076
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Complete Atrioventricular Block Complicating ST-Elevation Myocardial Infarction in Patients Undergoing Primary Percutaneous Coronary Intervention

Abstract: Objectives: ST-segment elevation myocardial infarction (STEMI) can be associated with many conduction disturbances including complete atrioventricular block (CAVB). CAVB complicating STEMI resulted in an increased mortality before the modern era of primary percutaneous coronary intervention (PCI). The aim of this study was to ascertain the rate and risk factors for CAVB in STEMI patients undergoing rapid reperfusion with PCI. Methods: We analyzed 223 patients presenting with STEMI. Patient characteristics, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…The incidence of complete AV block, the clinical characteristics of the patients, as well as the percentage of patients with an implanted temporary pacemaker (PM) are in keeping with the findings found in literature which relate to patients treated with pPCI (1,2,6,13). Complete AV block complicating STEMI in the pPCI era is most commonly registered at admission, as a part of acute ischemia.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The incidence of complete AV block, the clinical characteristics of the patients, as well as the percentage of patients with an implanted temporary pacemaker (PM) are in keeping with the findings found in literature which relate to patients treated with pPCI (1,2,6,13). Complete AV block complicating STEMI in the pPCI era is most commonly registered at admission, as a part of acute ischemia.…”
Section: Discussionsupporting
confidence: 81%
“…However, the difference disappeared after a year, which is why there was no difference in the mortality between the analyzed groups in the period between year one and year three of follow-up (13). Although most studies indicate that, in the pPCI era, complete AV predominantly affects intrahospital mortality in patients with STEMI, in a study by Chera et al, complete AV block was not found to be an independent predictor of in-hospital mortality (6). A similar finding can be found in a study by Lee et al, where the prognostic impact of complete AV block in patients with STEMI was analyzed, and it was not found that complete AV block influenced in-hospital mortality (14).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the current modern era of primary percutaneous coronary intervention, the incidence and in-hospital mortality rate of complete atrioventricular block in patients with STEMI who underwent primary PCI was reduced compared to the data from the thrombolytic era, and the incidence of complete atrioventricular block (CAVB) dropped to 3.2 and 4.6% [ 16 ] and 3.2% [ 17 ] in 2 separate studies. The risk factors of CAVB are age, worse Killip class at presentation, female sex, smoking, hypertension, and diabetes [16.17].…”
Section: Discussionmentioning
confidence: 99%